Relación entre trastornos psicológicos y consumo de sustancias psicoactivas en el CETAD CRADUN de la ciudad del Puyo, Provincia de Pastaza - Urquizo Noriega, Oswaldo Javier (2024)
The objective was set to determine the relationship between psychological disorders and the consumption of psychoactive substances in the CETAD CRADUN of the city of Puyo, province of Pastaza due to the growing problem of drug consumption throughout the country and the lack of knowledge of its repercussions. . on people's mental health. The research consisted of a correlational, exploratory and non-experimental study, where surveys were applied to 70 patients from CETAD CRADUN, this survey was made up of questions of a sociodemographic nature, consumption of psychoactive substances and questionnaires to determine the level of depression, anxiety, stress . , solitude and soil quality. It was found that the main substance consumed was alcohol with 29.17%, followed by marijuana and its derivatives with 19.05% and codeine and derivatives with 10.12%, also that most of the patients . They had levels: mild depression with 37.1%, moderate anxiety with 42.9%, normal stress with 65.7%, moderate loneliness with 78.6%, poor sleep with 85.7%. % %. The main substances were inhalants and solvents associated with stress and the use of sedatives and barbiturates with the feeling of loneliness. It is concluded that the levels of psychological disorders were mostly moderate or mild. Comprehensive care is recommended for the proper recovery of patients.